(untitled) (Prostor, 2022)
Architect Ernest Weissmann (1903-1985) dedicated his career to improving the living conditions of the deprived population - before and immediately after World War II in Europe and the United States and, starting from the 1950s and owing to senior positions he held at the United Nations Department of Social Affairs [UN DESA], also in underdeveloped countries in Asia, Africa, and Latin America. The means by which he tried to achieve it were type projects flexible enough to respond to each individual case, education, teamwork, and self-help approach. The latter was thought to strengthen the local communities, their experts, resources, and production. Relying on the research on Weissmann’s pre-UN DESA career, this paper argues that Weissmann formulated most of his ideas, in particular self-help, and the above-mentioned methods, and put them into practice and an international perspective, before 1951 thanks, to his collaboration with Le Corbusier, the School of Public Health in Zagreb, the International Congress of Modern Architecture [CIAM], New York-based Structural Study Associates [SSA] group, Board of Warfare, and United Nations Relief and Rehabilitation Administration [UNRRA].